2023
DOI: 10.1063/5.0133201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of downward seepage on turbulence and morphology in mobile boundary sinuous channel

Abstract: The porous boundary of alluvial channels allows water to interact with the surrounding groundwater. With the reduction in groundwater level, the transfer of water from the main channel to the groundwater is significant and referred to as downward seepage. The action of downward seepage at the boundary zones of sinuous bend causes morphological alteration along the sinuous alluvial channel. Laboratory experiments were conducted for no-seepage and seepage conditions to study the effect of downward seepage on tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Downward seepage can further complicate the problem by exerting an additional hydrodynamic force on the sediment particles and changing the hydrodynamic parameters of the channel. Previous researchers found that downward seepage plays a vital role in modifying the channel’s morphology 22 , 23 . Researchers suggested that permeable channels allow considerable water loss through the channel boundary, reducing the conveyance efficiency 24 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downward seepage can further complicate the problem by exerting an additional hydrodynamic force on the sediment particles and changing the hydrodynamic parameters of the channel. Previous researchers found that downward seepage plays a vital role in modifying the channel’s morphology 22 , 23 . Researchers suggested that permeable channels allow considerable water loss through the channel boundary, reducing the conveyance efficiency 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that a significant portion of the water that seeps into the ground and flows towards a stream is lost through the streambed. The study by 23 examined the effect of downward seepage on the mean streamwise velocity in curved channels. They observed that the presence of downward seepage caused an increase in the mean streamwise velocity at the centre of the channel.…”
Section: Introductionmentioning
confidence: 99%